LV twist predicts prognosis in children and adolescents with non-compaction cardiomyopathy. (8th February 2021) - Piccinelli, E; Sabatino, J; Krupickova, S; Fraisse, A; Prota, C; Bucciarelli, V; Avesani, M; Borrelli, N; Delle Donne, G; Josen, M; Paredes, J; Sirico, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left ventricular non-compaction cardiomyopathy (LVNC) is associated with poor clinical outcome in childhood, with heart failure, arrhythmias, and embolic events as main clinical manifestations. LV twist has recently been demonstrated having good predictive value in diagnosing LVNC in young patients. However, how LV twist may influence long-term clinical outcome of LVNC children and adolescents is still unknown. The aim of this study was to analyse a set of echocardiographic parameters to find imaging predictors of worse clinical outcomes in a long-term follow-up of LVNC children and young patients. Methods: Children and adolescents, followed from May 2012 to June 2020, were enrolled in a retrospective study. All patients underwent 2-dimensional speckle tracking echocardiography and cardiovascular magnetic resonance imaging (1.5 Tesla) at our Institution's first evaluation. Death, heart failure hospitalization, aborted sudden cardiac death, ventricular arrhythmias (sustained and non-sustained ventricular tachycardia), and embolisms (i.e. stroke, peripheral arterial embolism and/or pulmonary thromboembolism) were registered and referred to as major adverse cardiovascular events (MACEs). Results: Recruited for the study were 47 children (mean age: 11.1± 5; age range: 0–18 years). Twenty-three patients fulfilled the cardiovascular magnetic resonance imaging diagnostic criteria for LVNC (LVNC group), while the remaining 24 did not and were included in the LV hypertrabeculation group (LVHT). They were followed for 4.9 ± 1.0 years, and MACEs were registered. Thirteen children (56% of LVNC, 28% of total) had at least one MACE. Global longitudinal, circumferential and radial strains (GLS, GCS, GRS), LV twist and LVEF resulted being significantly reduced in children with MACEs at follow-up. A multivariable analysis was performed by combining four parameters: LV ejection fraction, GLS, GCS, LV twist. These independent variables were chosen according to univariable analyses and clinical relevance. The results from the analysis demonstrated that LV twist was the only independent predictor (P = 0.033, coeff. B 0.726) of worse clinical outcomes in young patients with LVNC. Conclusions: LV twist is a promising tool to stratify and predict prognosis in LVNC young patients. Our findings show the importance of LV twist assessment to detect the severity of LVNC and to plan for early clinical intervention.